SEKOLAH LUAR BIASA DENGAN PENDEKATAN BIOFILIK DI KOTA SINGKAWANG - Damayanti, Amelia Firda; Putro, Jawas Dwijo; Alhamdani, Muhammad Ridha (JMARS: Jurnal Mosaik Arsitektur, 2024)
Education is essential to every citizen's existence. It does not exclude those with impairments (differently abled). Article 5 of The Law of the Republic of Indonesia Number 20 of 2003 states, "Citizens with physical, emotional, mental, intellectual, and/or social disabilities shall have the right to special education." Special education is an education reserved entirely for pupils with disabilities (differently abled), including people who are blind, people who are deaf, people with quadriplegia, or people with psychiatric disabilities (mentally disabled). Certainly, every location contains individuals with disabilities. In order to fulfil the mandate of Article 5 of Law No. 20 of the Republic of Indonesia from 2003, people with disabilities deserve an education infrastructure that meets their needs. Due to this, special needs schools must be specifically constructed to provide teaching-learning activities that can aid in the development of the student's potential. The biophilic concept is one of a number of concepts that can be used to generate the aforementioned situation. Biophilic is an architectural idea that fosters a harmonious link between humans and nature. The objective of biophilic design is to create an environment that is conducive to the physical and mental growth of humans. Biophilic is employed because it may establish tranquility and calm through the building's connection to nature, and the application of this design is anticipated to improve the quality of education for students.